Banking on a Prize: Multicultural Capitalism and the Canadian Literary Prize Industry - Scott, Jennifer; Tucker-Abramson, Myka (Studies in Canadian Literature, 2007)
Critics such as Frank Davey and Barbara Godard note that the 1988 Canada-U.S. Free Trade Agreement introduced radical changes to the way the Canadian government supports domestic cultural production. One indicator is the primacy of the corporate-sponsored Giller Prize, part of a new cosmopolitan and free-trade-oriented cultural policy, over the government-funded Governor General’s Award, which is a creation and upholder of Trudeau-era multicultural policy. Free trade, accompanied by cuts to agencies such as the Canada Council and the CBC, has created only the illusion of separation between economic and cultural spheres. These cuts facilitated the corporatization of Canadian cultural policy, and resulted in a homogenizing of Canada’s literature. Proponents of awards like the Giller Prize often ignore what Smaro Kamboureli calls the “tight relationship” between economic and cultural control, and refuse to dig deep enough to ask who decides what is “good literature” and whose interests that literature serves.